ANALISIS HUBUNGAN ANTARA COPING STRATEGI DENGAN TINGKAT PENDAPATAN PETANI KARET DI KECAMATAN MESTONG KABUPATEN MUARO JAMBI - Oscar, Deny; Mara, Armen; Nainggolan, Saidin (JALOW | Journal of Agribusiness and Local Wisdom, 2018)
This research aims to: 1) to know the income level of rubber farmer in Mestong Sub-district of Muaro Jambi Regency; 2) to know the correlation between income level of rubber farmer with coping strategy In Mestong District Muaro Jambi Regency. The research was conducted in Suka Maju Village, Muaro Sebapo Village and Nyogan Village, Mestong District Muaro Jambi Regency. The sampling was conducted in two stages, the first stage is the stratified sampling method (Stratified Cluster Sampling), the second stage is the sampling is done by Non Probability Sampling with a total sample of 44 people. From the research results can be concluded that, 1) Rubber prices fluctuate, the highest price of rubber is in 2011 at the price level Rp 17.025 / Kg, while the lowest price is in 2015 at the price of Rp 4,500 / Kg. The difference between the highest and lowest price is Rp 12,525 or 333.3%. 2) There is a difference of income of rubber farmers in the research area with the expected, the amount of income is not sufficient so that need to do strategy to adapt to the economic pressure to meet the needs 3) There is a real relationship between the income level of farmers with "coping strategy" In overcoming the dynamics of rubber prices in Mestong Sub-district of Muaro Jambi Regency, where low-income farmers tend to do active.